Pemakaian Tindak Tutur Direktif dalam Khutbah Jumat dan Implementasinya Sebagai Materi Ajar Pembelajaran Pragmatik - Munah, Leni Mei; , Prof. Dr. Markhamah, M.Hum (2017)
Research on the Friday sermon aims to discover and describe the directive speech art in a Friday sermon and described implementation on pragmatic learning. This study uses rhe case study method, the data used is the recording of the sermon and then translated into writing. Data in this study are contained in the directive speech Friday sermon contained in the dara source. Data collection method and record the record. Data analysis using read many, a method that shows kejatian lingual unit specific or consistent identity. Results found in this study is speech acts directive as many as 19, the speech act directives govern as 6, the speech acts directives suggest as many 3, the speech act directive asking foe as much as 1, follow said directive prohibits many as 2, directive speech acts to woo as many as 2, the speech act as much as 2 and a directive reminding directive speech act calls for much as 1. Of the eight types of speech act is then implemented in learning pragmatic in the standard of competence that students are able to understand, respond to, explain, demonstrate and analyze matters relating to the discourse pragmatic include: understanding speech acts, understanding speech act directive,ant other types of directive speech act.